BERADAPTASI DENGAN KENDALA; PENELITIAN MENDALAM TENTANG BUDAYA KERJA GURU DI SEKOLAH-SEKOLAH PEDESAAN - Hasani, Nur Atika; Muhammad Mushfi El Iq Bali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze how teachers in rural schools adapt to various limitations and how work culture is formed under such conditions. The method used is a qualitative approach with a case study design, through in-depth interviews, observations, and documentation of teachers in several rural schools. The results show that limitations in infrastructure, access to technology, and high workload encourage teachers to develop adaptive strategies, such as informal collaboration, innovation in learning based on local resources, and increased role flexibility. The work culture that emerges tends to emphasize solidarity, creativity, and resilience.The implications of this study highlight the importance of more contextual policy support, training improvement based on local needs, and the provision of adequate facilities to strengthen the professionalism and well-being of teachers in rural areas.